PENGARUH KUALITAS PELAYANAN KEPERCAYAAN DAN RELIGIUSITAS TERHADAP LOYALITAS NASABAH DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING DI BAITUL MAAL WA TAMWIL (BMT) KOTA JAMBI - Dwi Lestari; Titin Agustin Nengsih; Fuad Rahman (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The research used a questionnaire method which was carried out at BMT Jambi City. This research used 100 samples as respondents with samples taken using Random Sampling Technique. The results of this research are: (1) Service quality has a significant effect on customer loyalty, (2) trust has a significant effect on customer loyalty, (3) religiosity has no significant effect on customer loyalty, (4) service quality has no significant effect on satisfaction, (5) ) trust has no effect on satisfaction, (6) religiosity has a significant effect on satisfaction (7) satisfaction has a significant effect on customer loyalty, (8) satisfaction does not mediate the effect of service quality on customer loyalty, (9) satisfaction does not mediate the effect of trust on customer loyalty ( 10) satisfaction does not mediate the effect of religiosity on customer loyalty